GTPase Rab5 and Rab7 proteins are modulated by Corynebacteriumpseudotuberculosis in murine macrophages - ROCHA FILHO, JOSÉ TADEU RAYNAL; Souza, Andréia de; Silva, Marcos; Trindade, Soraya; Vale, Vera; Meyer, Roberto (Revista de Ciências Médicas e Biológicas, 2024)
Abstract Introduction: Corynebacterium pseudotuberculosis is an intracellular facultative bacterium that affects macrophages, causing caseous lymphadenitis in goats and sheep. This disease is characterised by the formation of granulomas and results in significant economic losses for farmers of goats and sheep around the world. Phagosome maturation is essential for the death of intracellular pathogens, involving the fusion of the phagosome with early and late endocytic organelles, a process partially regulated by GTPase Rab5 and Rab7 proteins, respectively. Methodology: we evaluated the ability of an attenuated T1 strain and a wild-type C57 strain of C. pseudotuberculosis to alter Rab5 and Rab7 protein expression in peritoneal CBA mouse macrophages following in vitro infection. Results: Rab5 and Rab7 expression decreased in macrophages infected with the C57 strain compared to uninfected macrophages, while a significant reduction only in Rab7 expression was observed in cells infected with T1. Nonetheless, Rab5 and Rab7 expression was higher in macrophages infected with T1 than in cells infected with the wild-type C57 strain. Conclusions: our studies indicate a greater degree of modulation of the endosomal proteins directly involved in phagosome maturation by Corynebacterium pseudotuberculosis wild type. Keywords: Corynebacterium pseudotuberculosis; macrophages; phagolysosome; Rab proteins.